A pilot randomized controlled trial testing the effects of a routine‐based intervention on outcomes in a behavioural weight loss programme. (10th December 2015) - Demos, K. E.; Leahey, T. M.; Hart, C. N.; Trautvetter, J.; Coward, P. R.; Duszlak, J.; Wing, R. R.
Summary: Background: Structured routines aimed at eating and sleep have been successfully employed in weight loss interventions for children. Although such routines are discussed in lifestyle modification programmes for adults, they are not a primary focus. Purpose: The purpose of this study is to determine if establishing healthy eating and sleep routines may improve outcomes in a behavioural weight loss (BWL) intervention. Methods: Twenty‐five overweight/obese participants (age = 52.4 ± 9.8; body mass index = 33.5 ± 4.1) were randomly assigned to either a 4‐week routine‐based intervention (ROU) targeting regular eating and sleep or an education control before beginning an 18‐week BWL intervention. Results: Routine‐based intervention participants reported adhering to eating routines, with increased 'on‐schedule' eating ( p  = 0.007) and decreased 'off‐schedule' eating ( p  = 0.002) but showed no change in 'on‐schedule' sleep ( p  = 0.74). However, contrary to our hypothesis, ROU participants lost less weight than controls after 6 weeks of BWL (2.3 ± 2.5 vs. 4.6 ± 2.6 kg, p  = 0.04) and achieved only modest weight loss over the full 18 weeks (ROU: 3.2 ± 4.6 vs. education control: 5.8 ± 5.7 kg, p  = 0.23). Conclusions: Focusing initially on establishing healthy sleep and eating routines led to poorer, rather than better, subsequent weight loss outcomes. Further studies using a longer initial intervention period or focusing on only sleep or eating behaviour are needed to determine whether establishing routines for eating and sleep behaviours can enhance weight loss in adults.